Tough academic journey of research assistants in the Faculty of Education: PhD dissertation process - Karadag, Engin; Danisman, Sahin; Dulay, Sabiha; Bayir, Ozge Oztekin; Tekel, Esra (TUBA-TURKISH ACAD SCIENCES, 2018)
The aim of this study is to explore the reflections of PhD dissertation process on doctoral students who are research assistants by revealing their experiences. Eleven participants selected by maximum variation sampling method were included in this study designed as a case study. Data collected via semi-structured interview were analyzed as a descriptive analysis. The findings were presented under the themes as the role of advisor during the dissertation process, the control of dissertation process, the difficulty of the dissertation process and the effect of dissertation process to the life. According to the findings, advisors play a key role during dissertation process and they can affect the whole process in a positive or negative way. Although most of the participants asserted that students controlled most of the dissertation process, the others stated that students and advisors equally controlled the dissertation process. According to results, factors such as advisors, working conditions, defining dissertation topic, application, foreign language etc. were expressed as the difficulty of the dissertation process. As a result, dissertation process effect participants' life physiologically and psychologically in a considerable extent.
Keywords: Case study; PhD dissertation process; research assistants; DOCTORAL STUDENTS; SUCCESS; Education & Educational Research